Effect of non‐invasive brain stimulation on behavior and serum brain‐derived neurotrophic factor and insulin‐like growth factor‐1 levels in autistic patients. Issue 5 (18th March 2021) - Robinson‐Agramonte, Maria de los Angeles; Michalski, Bernadeta; Fernández, Lázaro Gomez; Vidal‐Martinez, Belkis; Cuesta, Hector Vera; Rizo, Carlos Maragoto; Fahnestock, Margaret
Abstract: Aberrant neural connectivity and intra‐cortical inhibitory dysfunction are key features of autism. Non‐invasive brain stimulation (NIBS) protocols have been proposed that modulate this aberrant plasticity. However, additional investigations are needed to evaluate the impact of this intervention on biological biomarkers of the disease. We recently demonstrated alterations in serum insulin‐like growth factor‐1 (IGF‐1) and brain‐derived neurotrophic factor (BDNF) immunoreactivity in subjects with autism compared to controls. The aim of this pilot study was to explore the change in serum levels of the neurotrophic factors BDNF and IGF‐1 in patients undergoing NIBS therapy. Sixteen subjects with autism spectrum disorder (ASD) were tested 1 week before and 1 week after NIBS to determine the short‐term outcome on behavior using the total score on the autism behavior checklist, autism treatment evaluation checklist, clinical global impression severity and the autism diagnostic interview. ASD subjects younger than 11 years old ( n = 11) were treated with transcranial direct current stimulation (tDCS), and those 11 years and older ( n = 5) were treated with repetitive transcranial magnetic stimulation (rTMS). Serum levels of BDNF and IGF‐1 were evaluated by Enzyme‐Linked Immuno‐Sorbent Assay before and after the intervention with NIBS. A significant reduction in scores on the clinical behavioral scales was observed in patients treated with NIBS (ABC‐T p = .002, CGI‐S p = .008, ADI‐T and ATEC‐T p < .0001). There was a trend towards reduced serum BDNF levels after NIBS ( p = .061), while there was no change in IGF‐1 levels. These data support further studies on the potential of BDNF as a biomarker to measure the effectiveness of NIBS in autism.